IMPLEMENTASI ASAS HUKUM PERJANJIAN TERAPEUTIK DALAM INFORMED CONSENT - Ramadhan, Muhammad Syahri (Istinbath : Jurnal Hukum, 2021)
Therapeutic Agreement is an agreement made because of an agreement between the Doctor and the Patient. Before this agreement is made and agreed upon by both parties, the patient is legally entitled to obtain information about any medical action that will be carried out by the Doctor to the Patient. This information is known as Informed Consent. It is important to apply the principle of therapeutic agreement, which is correlated with the availability of informed consent, so that medical actions taken by doctors against patients do not violate the law and/or cause disputes later. The first problem formulation of this research is how is the existence of informed consent in the legal principle of therapeutic agreement between doctor and patient, and what are the legal consequences if the legal principles of therapeutic agreement between doctor and patient are not implemented optimally. The result and discussion of this is that the existence of informed consent can be reviewed through the principles in contract law in general, namely the principle of good faith, the principle of proportionality and the principle of pacta sunt servanda. The principles of contract law are not implemented because there is no conformity of will between the doctor and the patient, where the doctor is process-oriented while the patient is results-oriented. The conclusion of this research is that Informed Consent should be a manifestation of the principle of pacta sunt servanda in an agreement in the form of Inspanning Verbintenis. The doctor can be said to have no good faith in carrying out the therapeutic agreement with the patient if he does not carry out one or all of the contents of the Regulation of the Minister of Health of the Republic of Indonesia concerning the approval of the medical action.